The ADB's Story - Nolan, Melanie (ANU Press, 2013)
'The Australian Dictionary of Biography captures the life and times and culture of this country in an absolutely distinctive and irreplaceable way. It is the indispensable record of who we are, and of the characters who have made us what we are. I could not be prouder of ANU's continuing role as custodian of this crucial part of our national legacy.' Professor the Hon. Gareth Evans AC QC, Chancellor, The Australian National University 'A mature nation needs a literary pantheon of inspiring and instructive life histories, a gallery of all the possibilities of being Australian. The Australian Dictionary of Biography responds to that vital need in our culture. It is a stunning collaborative achievement and I feel so proud that we have such an activity here in Australia-to a great extent it describes and defines Australia.' Professor Fiona Stanley AC, Australian of the Year, 2003 'The Australian Dictionary of Biography is our greatest collective research project in the humanities and a national triumph. We have much to learn from it. The project is continuing to change as we mature nationally, with deeper understanding about the impacts of gender, race, environment, religion, education, language, culture, politics, region and war on what we are and what we may become.' The Hon. Dr Barry Jones AO 'Australia is very fortunate to have a national biographical dictionary that is democratic as well as distinguished, one that represents the rich variety of Australian culture. The Australian Dictionary of Biography gathers together the stories of people from all walks of life, from the outback to the city and from the bush to the parliament. It is a monument of scholarship-and it is for everyone.' Dr Dawn Casey PSM 'Few things are more illuminating than taking a random stroll through a volume of the Australian Dictionary of Biography-new insights into our greatest men and women, chance encounters with people whose exploits are all too often unpardonably overlooked. I first read the ADB with my mother, Coral Lansbury, who wrote four entries. One of her mentors, Bede Nairn, was a prodigious contributor. The Australian story is a story of Australians, no better told than in the ADB.' The Hon. Malcolm Turnbull MP 'I find it difficult to bring to mind more than a handful of comparable enterprises in the fields of biography, history, philology or the social sciences more broadly-anywhere in the world. The status and appeal of the Australian Dictionary of Biography do not lie only in its scale and size. They reside also in the meticulous research, the erudition and scholarship, and the sweat and possibly tears involved in the editorial and publishing process. Its constituent dramatis personae are an eclectic mix of the noble and the notorious, the famous and the largely unsung. The underlying theme of the mosaic is quite clear: nothing less than the making and remaking of Australia.' Her Excellency Ms Penelope Wensley AC, Governor of Queensland